Java : first contact - Garside, Roger, 1944-; Mariani, John. (Boston : International Thomson Computer Press, 1997)
This book contains six parts: Using objects; Writing objects; Advanced objects; Advanced java; Object-oriented design; and Appendices.
Keywords: Java; Computer program language; Java (Computer program language)